Zmĕny tĕlesných tekutin a minerálií po chladové adaptaci - Srámek, P; Ulicný, B; Janský, L; Zeman, V; Osanec, J (Casopis lekaru ceskych, 1993)
To characterize fluid and ion shifts during 5-weeks cold adaptation, 6 nonadapted volunteers underwent cold acclimation programme (CAP), consisted of 1 h head-out immersion in water 14 +/- 1 degrees C 3 times a week. Blood samples were analyzed before/after the immersion and in the first and in the last week of CAP. Urine was collected for 10 h before, during, and after immersion for 4 h. Plasma volume (PV) decreased during first immersion (-18%) and less after CAP (-12). Blood volume reduction was 8.5% before and 5.2% after the CAP. Mean corpuscular volume was not changed either after the cold exposition or after the cold adaptation. The concentration of serum proteins increased by 12.1% after first immersion and by 8.1% after the CAP. The changes in serum concentration of Na+, K+ and Cl- before and after the CAP were not significant. Urine flow increased by 102% after first immersion, and by 165% after CAP. Urinary excretion of Na+ increased by 167% and 283%, excretion of K+ by 222% and 362% during first immersion and after CAP, respectively. Serum concentration of aldosterone increased nonsignificantly (+30%) during immersion before CAP and it did not changed after CAP. After the cold adaptation we observed the reduction of PV decrease, and increased diuresis with higher excretions of cations.
Keywords: krevní objem; aklimatizace; Adult; dospělí; nízká teplota; ponoření; Blood Proteins; Urine; krevní proteiny; Acclimatization; Humans; moč; Immersion; lidé; Electrolytes; Blood Volume; elektrolyty; Cold Temperature